2021
DOI: 10.1093/glycob/cwab123
|View full text |Cite
|
Sign up to set email alerts
|

The tumor-associated Tn antigen fosters lung metastasis and recruitment of regulatory T cells in triple negative breast cancer

Abstract: Cancer is a leading cause of death worldwide, accounting for nearly 10 million deaths. Among breast cancers (BC) subtypes, triple-negative (TN) BC, is characterized by metastatic progression and poor patient prognosis. Although, TNBC is initially sensitive to chemotherapy, many TNBC patients rapidly develop resistance, at which point metastatic disease is highly lethal. Cancer cells present phenotypic changes or molecular signatures that distinguish them from healthy cells. The Tn antigen (GalNAc-O-Thr/Ser), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Tn antigens and shorter linear mucin-type O-glycan core structures, typically found on cancer cells in patients with poor prognosis, 54,55 were better recognized by all sera compared to the peptides with extensive glycosylation with branched core 2 and core 4 structures, typically found on healthy cells. These latter diminished antibody recognitions of all antisera (Figure 8), suggesting that vaccine conjugates preferentially induced a tumor-specific humoral immune response.…”
Section: Mgl Binds Vaccine Constructs and Mediates Antigen Uptake In ...mentioning
confidence: 90%
“…Tn antigens and shorter linear mucin-type O-glycan core structures, typically found on cancer cells in patients with poor prognosis, 54,55 were better recognized by all sera compared to the peptides with extensive glycosylation with branched core 2 and core 4 structures, typically found on healthy cells. These latter diminished antibody recognitions of all antisera (Figure 8), suggesting that vaccine conjugates preferentially induced a tumor-specific humoral immune response.…”
Section: Mgl Binds Vaccine Constructs and Mediates Antigen Uptake In ...mentioning
confidence: 90%
“…Early preinvasive and invasive pulmonary GGNs are adenocarcinomas that are smaller than 3 cm in diameter, with pathological types have conducted extensive research on intrapulmonary GGNs. However, the focus of each study is different, the inclusion criteria for GGNs and the grouping criteria for lesion types are not consistent, the evaluation of nodule imaging signs is subjective Therefore, the objective of this study was to systematically evaluate the quality of previous studies and to analyze the diagnostic value of the size, density, vacuole, burr, lobular, and pleural depression signs in early preinvasive and invasive intrapulmonary GGNs in high quality literature (25). Some studies have investigated other observational indicators, such as lesion volume, quality, and relationship with blood vessels or bronchi, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed Tn + colorectal gliomas infiltrated with MGL + TAMs are characterised by an enhanced accumulation of MDSCs and reduced levels of cytotoxic CD8 + T cells [207]. In addition, our group has recently demonstrated that both lung and breast tumours expressing the Tn antigen contribute to immune evasion by inducing the recruitment of MGL + cells that produce IL-10 and favour the differentiation of tumour-infiltrating Tregs [124,208]. Interestingly, Tn + lung tumour cells also contribute to tumour angiogenesis.…”
Section: Minclementioning
confidence: 98%